The “Conscience of the Self” and Its Infallibility From the Perspectives of Muslim Philosophers - Maytham ʿAzīzīyān Muṣliḥ; Sayyid Murtaḍā Ḥusaynī Shāhroudī (آموزه‌‌های فلسفه اسلامي, 2024)
One of the examples of the intuitive knowledge (Arabic: عِلْمُ الْحُضوری, lit.: knowledge by presence or presential knowledge) is “self-consciousness”. There are two important epistemological questions regarding this concept: First, do we have a consciousness of a reality called “self”? Second, is this consciousness infallible, accurately reflecting the reality of “self” as it is, or could “consciousness of self” be at odds with the “objective self”? There are two basic innovative points in response to these two issues that are considered in this article. First, Muslim philosophers recognize a hierarchy for the knowledge of the “self,” in which the most basic and fundamental aspect of consciousness regarding the “self” is the “perception of the self.” This approach plays an important role in countering the deniers of the “conscious self.” Second, from this perspective, the only way to discuss the most fundamental level of knowing the “self” (the understanding of the self) is to describe one’s consciousness with the aid of descriptive reason. Within the framework of these two points, it can be said that, first, there is a consciousness of the “perceiving self,” and second, the Muslim philosopher, as a deep foundational thinker, regards this consciousness as a “reality.” Due to the unity of consciousness and reality, he concludes that the “epistemic awareness of the self” cannot deviate from the “objective self.” Moreover, considering the “epistemic awareness of the self” and the “objective self” as one is not merely a matter of convention, but rather relies on the content of “consciousness of self” (the understanding of the self).